(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
This paper addresses the sources of stress that military personnel face and discusses the variables that serve to buffer its impact on health, safety and effective job performance. These variables (such as a positive outlook, positive thinking, coping strategies, self-control, realism, personality hardiness, self-efficacy, altruism and spirituality, amongst others) are being incorporated by the different surrounding armed forces into psychological strengthening programmes for their staff (for instance, the programmes Comprehensive Soldier Fitness or Trauma Risk Management). In this spirit, one variable that is proving to be of great relevance is leadership. Transformational leadership shields well against occupational stress, yet its application in rigid or excessively hierarchical organisations, such as armies, often comes under question. The alternative lies in value-based leadership styles (for instance, ethical leadership and authentic leadership)